Senile pseudoexfoliation in aphakic eyes. - Radian, A B (1975)
In three eyes which underwent cataract extraction no evidence of senile pseudoexfoliation was found either before, or immediately after, surgery in spite of repeated biomicroscopical examination under full mydriasis. Years later pseudoexfoliative material was found on the anterior hyaloid and on the pupillary border. In another case, wherein the lens was traumatically dislocated and had lain in the inferior vitreous chamber for 53 years, pseudoexfoliative material was present on the anterior hyaloid, but not in the vitreous. Collating these clinical observations with data from electron and light microscopy studies, the authors refute the assumption that lens epithelium is the source of pseudoexfoliative material.